Towards a model of new and emerging occupational risks for small and medium enterprises (SMEs) - Nur Fazrina, Mohamad Salleh; Ezrin Hani, Sukadarin; Hanida, Abdul Aziz (Taylor and Francis Ltd., 2025)
The new and emerging risk (NER) model assists small and medium enterprises (SMEs) in identifying NER at their workplace. This study employed the fuzzy Delphi method (FDM) to validate the risk categories, groups, and associated risks derived from the EU-OSHA expert forecast report, systematic literature review and interviews. The result indicates all four NER of psychosocial, chemical, physical and biological categories with 91 associated risks reached the expert consensus (thresholds value (d) ≤ 0.2, expert agreement ≥ 75% and fuzzy evaluation (A) ≥ 0.5). It is signifying that the NER model in SMEs should include four categories, 19 groups, and 91 associated risks. This study also displayed minor variations compared to other workplace issues, such as precarious employment, bullying, violence, presenteeism, and others, which are not classified as NER. Considering the study of NER is limited, this model offers significant associated NER in SMEs and can be used as a reference in their efforts to identify and prevent risks adequately.